Microbiota aeróbia do sêmen e da mucosa prepucial e efeito dos antimicrobianos na conservação dos parâmetros espermáticos de catetos (pecari tajacu linnaeus, 1758) em cativeiro - Santos, Caio Sérgio (Universidade Federal Rural do Semi-Árido, 2020)
The presence of bacteria in the semen can cause losses in sperm function and, consequently, interfere with reproductive biotechnologies that make use of this biological material. That said, the objective was to describe the aerobic bacterial microbiota of captive collared peccaries (Pecari tajacu) semen and foreskin, as well as the impact of the use of antimicrobial substances on the bacterial load and sperm function during the semen conservation of this species. In the first experiment, aerobic bacteria were cultured in semen and foreskin samples from nine animals, as well as their quantification and evaluation of sperm parameters in the semen. The isolates were identified and tested against concentrations of penicillin-streptomycin, gentamicin and Aloe vera gel. Corynebacterium spp. and Staphylococcus spp. were isolated in greater numbers in semen (64.1% and 20.5%, respectively) and in the foreskin (60.6% and 24.2%, respectively), ranging from 0.4 to 21 × 105 colony-forming units (CFU) per milliliter. The load of Corynebacterium spp. it was negatively correlated (P <0.05) with the integrity of the sperm membrane (r = −0.73055) and curvilinear velocity (r = −0.69048). The combination of streptomycin-penicillin (SP) and gentamicin (G) inhibited the majority of microorganisms and A. vera demonstrated a weak antimicrobial potential. In the second experiment, the toxicity of antimicrobials on sperm longevity was analyzed by the thermoresistance test in six semen samples, each diluted in Tris alone (control) and Tris plus the streptomycin-penicillin combination (2 mg/mL - 2000 IU/mL) or gentamicin (70 μg/mL), and maintained for 180 min at 37 °C. It was found that the treatments did not differ (P > 0.05) until 180 min, but that the treatment containing G reduced (P < 0.05) the sperm membrane integrity and mitochondrial activity at 180 min (53, 1 ± 7.1% and 50.7 ± 6.2%, respectively) if compared to 0 min (80.5 ± 4.7% and 86.3 ± 3.4%, respectively). In the third experiment, the effect of two concentrations of SP (2 mg/mL - 2000 IU/mL [2] and 1 mg/mL - 1000 IU/mL [1]) and G (70 μg/mL [7] and 30 μg/mL [3]) added to Tris + 20% egg yolk (TE) and Tris + 20% A. vera (TA) diluents on bacterial load and sperm quality in 10 semen samples kept under refrigeration (5 ° C) up to 36 h. The treatment containing SP2, SP1 and G7, regardless of the diluent, controlled (P < 0.05) the bacterial growth during storage (ranging from 0.5 ± 0.3 103 to 10 ± 4.1 x 103 CFU/mL) up to 36 h. Treatments diluted with TE with any of the antimicrobials showed no differences (P > 0.05) for bacterial load and sperm parameters between 0 and 36 h. TA treatments, with or without antimicrobials, affected (P < 0.05) the sperm membrane integrity and mitochondrial activity after 12 h. The TE-G7 treatment stood out for maintaining some sperm variables for a longer time, such as total motility (41.9 ± 6.1%) and progressive (15 ± 2.6%) up to 24 h, as well as membrane integrity (58.3 ± 2.1%) and curvilinear velocity (76.7 ± 5.8%) up to 36 h. Given the results, it was demonstrated the occurrence of bacterial contaminants in semen and foreskin peccaries bred in captivity, especially Corynebacterium spp. and Staphylococcus spp., as well as a negative impact of the first on sperm function in fresh semen. The streptomycin-penicillin combination (2 mg/mL - 2000 IU/mL) and gentamicin (70 μg/mL) can be added to Tris in the semen dilution, incubated at 37 °C for up to 120 min, without causing toxic effects to sperm. These drugs were also effective in controlling the bacteria present in the refrigerated semen of these animals, for up to 36 h, without affecting sperm longevity
Keywords: Aloe vera; Bactérias; Refrigeração; Termo-resistência; Aloe vera; Bacteria; Refrigeration; Thermoresistance; CIENCIAS AGRARIAS::MEDICINA VETERINARIA